INNOVATIVE ACTIVITY IS A FACTOR THAT DEVELOPS THE MAIN SPHERES OF THE ECONOMY - Jabriyev, Akbar; Egamov, Rakhmatillo (International Journal of Psychosocial Rehabilitation, 2020)
The article discusses innovation – a process issues of providing construction products on the basis of innovative measures. In this regard, the author gives some approaches to ensuring the competitiveness of construction products on the basis of innovative measures.